Mr. Watson's chickens - Dapier, Jarrett (Chronicle Books, 2021)
Mr. Watson loves his three chickens, and every morning he and Mr. Nelson count them; but when they start to multiply, his house and tiny yard are soon overrun, and the noise and mess are driving Mr. Nelson crazy--so the couple set out to find a new home for the chickens.